Early-Life Exposure of Pigs to Topsoil Alters miRNA and mRNA Expression in Peripheral Blood Mononuclear Cells - De Souza, M. M.; Koltes, D. A.; Beiki, H.; Sales, M. A.; Tsai, T.; Maxwell, C. V.; Zhao, J.; Koltes, J. E. (Frontiers in Genetics, 2022)
Exposure to less hygienic conditions during early childhood has been associated with stimulation and development of the immune system. A recent study indicated exposure of piglets to soil-borne microbes during lactation was related with modulation of gut microbiota and immune function. To identify potential molecular mechanisms and pathways impacted by early life topsoil exposure, we analyzed messenger RNA (mRNA) and micro RNA (miRNA) expression in peripheral blood mononuclear cells (PBMC) from these piglets. Total RNA was extracted from PBMC of piglets exposed to topsoil only from d 4-d 21 of life (mRNA n=6; miRNA n=5) or unexposed control pigs (mRNA n=6; miRNA n=8) at 11, 20, and 56 days of age. Small RNA and mRNA were sequenced with 50-bp single-end reads using Illumina chemistry. Sequence data were quality checked with FASTQC software and aligned to the Sscrofa 11.1 genome with the STAR aligner for mRNA and mirDeep2 for miRNA. Differential expression (DE) analysis was performed using PROC Glimmix of SAS to evaluate changes in expression due to topsoil exposure over time with genes declared DE at a false discovery rate (FDR) of q<0.10. A total of 138 mRNA and 21 miRNAs were identified as DE for the treatment by age interaction. Ontology enrichment analysis of DE mRNA revealed Gene ontology (GO) terms directly involved in the connection between T-cell and antigen-presenting cells that are associated with T-cell activation. Key regulatory genes identified include PTPRJ, ITGB3, TRBV30, CD3D, mir-143, mir-29, and mir-148a. While these results require validation, this study provides data supporting the hypothesis that less hygienic environments during early life may contribute to the development of the immune system.